2009
DOI: 10.1016/j.fct.2008.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic neurotoxicity induced by methylmercury and quercetin in mice

Abstract: Methylmercury (MeHg) is a highly neurotoxic pollutant, whose mechanisms of toxicity are related to its pro-oxidative properties. A previous report showed under in vivo conditions the neuroprotective effects of plants of the genus Polygala against MeHg-induced neurotoxicity. Moreover, the flavonoid quercetin, isolated from Polygala sabulosa, displayed beneficial effects against MeHg-induced oxidative damage under in vitro conditions. In this study, we sought for potential beneficial effects of quercetin against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…As a by-product of its antioxidant activity, quercetin is oxidized; if the glutathione concentration is not high enough, the potential oxidative reactions induced by quercetin will be focused on the protein thiols [16]. Martins et al [21] showed that quercetin administration potentiates the oxidative damage induced by methylmercury in mouse cerebellum. This effect was found together with unchanged levels of cerebellar glutathione and glutathione reductase activity induced by quercetin and methylmercury separately and when both treatments were combined.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As a by-product of its antioxidant activity, quercetin is oxidized; if the glutathione concentration is not high enough, the potential oxidative reactions induced by quercetin will be focused on the protein thiols [16]. Martins et al [21] showed that quercetin administration potentiates the oxidative damage induced by methylmercury in mouse cerebellum. This effect was found together with unchanged levels of cerebellar glutathione and glutathione reductase activity induced by quercetin and methylmercury separately and when both treatments were combined.…”
Section: Discussionmentioning
confidence: 98%
“…Quercetin's major circulating compounds in plasma were identified as quercetin 3-O-glucuronide, 3′-Omethylquercetin 3-O-glucuronide, and quercetin 3′-O-sulfate [32]. Once quercetin metabolites reach the blood flow, they are able to transverse the blood-brain barrier and are subsequently accumulated in the brain [33], where they exert their biological effects on the cerebellum [21,34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, quercetin is reported to be a safe compound and there is no scientific report on its carcinogenicity as well as genotoxicity after oral administration of quercetin even at high doses (up to 2000 mg/kg) (Harwood, Danielewska-Nikiel, Borzelleca, Flamm, Williams, & Lines, 2007). Despite these considerations, quercetin has synergistic effects with methylmercury for its neurotoxicity (Martins, Braga, da Silva, Dalmarco, de Bem, dos Santos, et al, 2009). It has also been reported that in spite of the anti-inflammatory effect of quercetin, it resulted in also showing pro-inflammatory effects under in vivo conditions (Nicolau, Dovichi, & Cuttle, 2003).…”
Section: Quercetin As a Food Supplementmentioning
confidence: 99%
“…Such symptoms were also observed in experimental studies using cats (Charbonneau et al, 1976), dogs (Mattsson et al, 1981), mice (Inouye et al, 1985; Dietrich et al, 2004); rats (Rocha et al, 1993; Farina et al, 2005), monkeys (Rice, 1996) and zebrafish ( Danio rerio ) (Samson et al, 2001). Although experimental studies on MeHg-exposed animals have shown that behaviors related to visual (visual contrast sensitivity task; Burbacher et al, 2005), cognitive (passive avoidance task; Ferraro et al, 2009) and emotional (depression-like behavior evaluated in the forced swimming test; Onishchenko et al, 2007) functions are also affected by MeHg exposures, movement disorders , consisting mainly of ataxia and loss of balance, have been extensively reported in experimental studies using MeHg-exposed animals (Dietrich et al, 2004, Farina et al, 2005; Lucena et al, 2007) and have been used as an important behavioral parameter to correlate with histological/cellular damage and/or biochemical changes (Franco et al, 2006; Carvalho et al, 2007, Carvalho et al, 2008), as well as to study potential protective/antidotal strategies to counteract MeHg-induced toxicity (Farina et al, 2005; Martins et al, 2009). …”
Section: Behavioral Hallmarksmentioning
confidence: 99%